A shocking-red new species of Setanodosa Salmon, 1942 (Collembola: Brachystomellidae) from South Africa - Janion-Scheepers, Charlene; Deharveng, Louis (Zootaxa, 2022)
A new species of Setanodosa, S. jacquesi sp. nov. is described from the Western Cape (South Africa). It differs from other species of the genus by its unique shocking red pigmentation, the number of vesicles in the post antennal organ, and the number of clavate tenent hairs on the tibiotarsi. A comparative table of the world Setanodosa and a key of Brachystomellidae species known from South Africa are provided. DNA barcoding results are provided for several Brachystomellidae species from South Africa, Australia and the sub-Antarctic to support our findings. It shows that a species provisionally identified as Brachystomella cf. platensis is unambiguously present in both South Africa and Australia.